ChemInform Abstract: Terpenoids from the Stems of Drypetes congestiflora. Issue 42 (October 2015) - Chen, Wen‐Hao; Han, Chang‐Ri; Hui, Yang; Zhang, Da‐Shuai; Song, Xin‐Ming; Chen, Guang‐Ying; Song, Xiao‐Ping
Abstract isolation, structure elucidation and cytotoxicity of two new eremophilane‐type sesquiterpenoids (I), (II), a new friedelane‐type triterpenoid (III) along with six known triterpenoids